Peroxynitrite biochemistry oxidation and nitration reactions - Radi, Rafael (Henry Stewart Talks, 2018)
Nitric oxide reaction with superoxide radical: the formation of peroxynitrite, Peroxynitrite-mediated thiol oxidation, Peroxynitrite decomposition pathways: one vs two-electron oxidation processes, Thyl radicals and sulfenic acids, Peroxynitrite kinetics and stopped flow analysis, Peroxynitrite reaction with fact reaction thiols, the case of peroxiredoxins, Peroxynitrite reaction with transition metals, The reaction of peroxynitrite with carbon dioxide: the formation of carbonate radicals, Proton-catalyzed homolysis of peroxynitrite to hydroxyl radicals, Lipid peroxidation and nitration, Protein tyrosine nitration, a free radical process, Protein tyrosine nitration in disease states, Peroxynitrite and mitochondrial dysfunction, Role of peroxynitrite in pathology, Peroxynitrite therapeutics